Escolítidos (Coleóptera Scolytidae) asociados al agroecosistema cacao en tabasco Mexico - Pérez de la Cruz, M.; Equihua Martínez, A.; Romero Nápoles, J.; Sánchez Soto, S.; García López, E.; Bravo Mojica, H. (CATIE, Turrialba (Costa Rica), 2015)
2 ilus. 4 tab. 21 ref.